2015
DOI: 10.1186/s13287-015-0192-0
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy of menstrual derived mesenchymal stem cells and antibiotics ameliorates survival in sepsis

Abstract: IntroductionSepsis is a clinical syndrome associated with a severe systemic inflammation induced by infection. Although different anti-microbial drugs have been used as treatments, morbidity and mortality rates remain high. Mesenchymal stem cells (MSCs) derived from the bone marrow have demonstrated a partial protective effect in sepsis. Menstrual derived MSCs (MenSCs) emerge as an attractive candidate because they present important advantages over other sources, including improved proliferation rates and para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
174
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 132 publications
(181 citation statements)
references
References 46 publications
7
174
0
Order By: Relevance
“…Consistently with previous reports [29, 31, 32, 37], MenSCs express CD105, CD44, CD73, CD90 and HLA-ABC, but showed negative expression for CD45, CD34, CD14 and HLA-DR (Figure S1 A). Also, mesodermal lineage induction showed positive specific staining for fat, bone and cartilage differentiation (Figure S1 B).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Consistently with previous reports [29, 31, 32, 37], MenSCs express CD105, CD44, CD73, CD90 and HLA-ABC, but showed negative expression for CD45, CD34, CD14 and HLA-DR (Figure S1 A). Also, mesodermal lineage induction showed positive specific staining for fat, bone and cartilage differentiation (Figure S1 B).…”
Section: Resultssupporting
confidence: 92%
“…Menstrual fluids and bone marrow were obtained after informed consents following institutional guidelines from four healthy donors aged 24-38 years-old and two hip-operated patients aged 60-68 years-old, respectively [29, 31]. MSCs were isolated, cultured, and characterized as described previously [29, 31, 32], and cryopreserved at low passage (< 5) until use. Human umbilical vein endothelial cells (HUVEC), human pancreas adenocarcinoma MIA PaCa-2, human pancreas carcinoma PANC-1, metastatic human breast cancer MD-MB-231, metastatic human breast cancer MCF-7, metastatic human prostate adenocarcinoma PC3, metastatic human prostate carcinoma DU 145, metastatic human prostate carcinoma LNCaP and metastatic human prostate cancer VCaP cell lines were obtained from the American Type Culture Collection (ATCC, Manassas, VA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, current data suggest that MSCs exert strong antimicrobial effects through indirect and direct mechanisms (1626). Indirectly, across their role in the host immune response against pathogens, especially in the dynamic coordination of the pro- and anti-inflammatory elements of the immune system (22, 2729) or increasing the activity of phagocytes (18, 21, 25, 30, 31); and directly, by the secretion of antimicrobial peptides and proteins (AMPs) (19, 20, 23, 24, 26), and also by the expression of molecules such as indoleamine 2,3-dioxygenase (IDO) (16) and interleukin (IL)-17 (32). In fact, MSCs have been reportedly responsible of the bacterial clearance in preclinical models of sepsis (1720, 22, 25), acute respiratory distress syndrome (ARDS) (21, 26), and cystic fibrosis infection (23).…”
Section: Introductionmentioning
confidence: 99%
“…These molecules have selective activity against a wide range of organisms including bacteria, yeasts, fungi, viruses, and even cancer cells (34). So far, MSCs have been found to constitutively express four AMPs: cathelicidin LL-37 (19, 23), human β-defensin-2 (hBD-2) (24), hepcidin (20), and lipocalin-2 (Lcn2) (26), which can be further modulated during infection and inflammation. In fact, it has been demonstrated that, in MSCs, a bacterial preconditioning induces an upregulation of LL-37, hBD-2, and hepcidin (19, 20, 24), while their preconditioning with inflammatory stimuli evoke increasing levels of LL-37 and Lcn2 (23, 26).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation